The tensile stiffness of a novel anchored blind-bolt component for moment-resisting connections to concrete-filled hollow sections - Pitrakkos, Theodoros (2012)
The use of hollow section columns in steel construction is presently hindered by the lack of adequate connection technologies. Due to access constraints, standard bolting techniques are difficult to achieve, if not impossible without welding. As an alternative to welding, blind-bolting techniques were developed to provide desirable bolted configurations, allowing hollow column frames to be erected in the same way as open profile column frames. But the current blind-bolting techniques are restricted to the construction of simple connections because of their difficulties in achieving sufficient tensile stiffness.